Noncausal effects between tea intake and migraine risk: a Mendelian randomization study - Chen Jin; Sijing Tu; Siyi Sun; Zhongyi Zhang; Xiaohe Wang (Scientific Reports, 2023)
Abstract Observational studies have yielded conflicting results regarding the relationship between tea intake and migraine risk. Residual confounders and potential reverse causality are unavoidable in traditional observational studies. To provide evidence for establishing viable disease screening and prevention strategies, a Mendelian randomization study (MR) was conducted to determine the causal inference between tea intake and migraine. We obtained 28 single-nucleotide polymorphisms (SNPs) for any migraine (AM), 25 SNPs for migraine with aura (MA), and 27 SNPs for migraine without aura (MO) associated with tea intake derived from a large genome-wide association study (GWAS) of the UK Biobank (UKBB) (containing 447,485 samples). The largest migraine GWAS performed by the International Headache Genetics Consortium (IHGC), including 29,209 cases and 172,931 controls, provided data on migraines and their subtypes (MA and MO). We used the method of inverse variance weighting (IVW) with fixed effects as the first-string MR selection. Sensitivity analysis and MR-pleiotropy residual sum and outlier (MR-PRESSO) method further assessed the robustness of the findings. Based on the conclusion of IVW in the fixed effects model, we found that tea intake had no causal relationship with AM risk (odds ratio (OR), 0.94; 95% confidence interval (CI), 0.70–1.25; P = 0.65), MA risk (OR, 0.93; 95% CI, 0.51–1.72; P = 0.83), or MO risk (OR, 0.90; 95% CI, 0.52–1.54; P = 0.69). Sensitivity analyses and MR-PRESSO showed no directional pleiotropy or heterogeneity. Our two-sample MR investigation found no causality between tea intake and migraine risk in European populations, implying that attempts to change tea drinking habits may not lead to a reduced risk of migraine.